Designing pedagogical narrative stories: Delving deeper into problem-solving skills of pre-service English teachers - Ginting, Aprilia Arnis; Kuswandono, Paulus (Universitas Muhammadiyah Sidoarjo, 2020)
Educating Pre-Service English Teachers (PSETs) to be ready to face challenges is a response to the fast changing globalized world. Hence, preparing future teachers to apply problem-solving skills in dealing with teachers’ challenges in the classroom is necessary. This study was intended to design a set of pedagogical narrative stories which enquire problem-solving skills of PSETs. The pedagogical narrative stories were designed as a supplementary material in micro teaching class to help PSETs understand the complex issues of teaching and learning process. This study was based on ADDIE model. The designed material product consists of six units of teachers’ real life in adapted stories. Each unit contains critical discussion and reflective activities namely: Story, Individual Reflection, Group Sharing, Class Discussion and Resolution. The final product was validated by subject matter expert who has credibility in writing English learning books. The validated outcome showed that the supplementary materials are appropriate for PSETs in micro teaching class. The finding is projected to construct positive awareness on the importance of problem-solving skills to enhance PSETs’ competence in dealing with classroom problems by answering questions more critically and reflectively. HIGHLIGHTS: · Problem solving skills can support PSETs in dealing with unpredicted occurrences beyond mastering knowledge and teaching materials in class. · Factual problems and guided reflections can provide PSETs with story engagement that is close to the real life of becoming teachers. · Through reflective practices, PSETs have opportunities to evaluate and make meaning of their previous educational experiences to become decision makers.